EKSTRAKSI TANAMAN OBAT KELUARGA TEMU HITAM (Curcuma aeruginosa Roxb.) SEBAGAI UPAYA PENAMBAH NAFSU MAKAN ANAK - Yauwan Tobing Lukiyono; Ersalina Nidianti; Salfa Salsabilah Zain (JOURNAL OF PHARMACY SCIENCE AND TECHNOLOGY, 2023)
Indonesia is one of the countries in the world that has very diverse and very large amounts of wealth, such asÂ  plants. As for the wealth of plants in question, such as the existence of plants that have properties for body health and growth and development. Many mothers and caregivers complain about decreased appetite because if energy and nutritional needs are not met there will be a slowdown in physical growth, mental development and mental retardation. One of the plants that can be used to increase appetite is black temu (Curcuma aeruginosa Roxb). Black rhizome belongs to the Zingiberaceae family, contains black compounds including essential oils, tanim, curikumol, kurkumenol, isokurkumelon, kurzerenon, kurdion, kurkumolactone, germakron and curcumin. The purpose of this research is to find out further benefits and prove whether the content of black rhizome can increase appetite in children. This study uses the literature method by seeking various sources from previous studies. The results obtained show that the content of essential oils has the potential to reduce fat so that it can trigger appetite, while the content of curcuminoids can cause relaxation of the intestine in the gastrointestinal tract which can help digestion of food and absorption of food ingredients by increasing the work of the stomach so that the stomach feels empty. The conclusion obtained is that these two ingredients can increase appetite in children so that they can get their appetite back and the energy and nutritional needs of their ody will be fulfilled perfectly.